EGO SINTONIK TOKOH-TOKOH HOMOSEKSUAL DALAM NOVEL INDONESIA MODERN - Iswadi Bahardur (Puitika)
This research aimed to describe the human  sintonik ego problem with homosexual acts, especially the figure in modern Indonesian novel.  The data source  is novel Saman dan Larung by Ayu Utami, Nayla by Djenar Maesa Ayu, Dadaisme by Dewi Sartika, Tabula Rasa by Ratih Kumala, Lelaki Terindah By Andrei Aksana, Cermin Cinta by N. Riantiarno, and The Sweet Sins by Rangga Wirianto. The result showed that homosexual character; gay (homosexual male designation) and lesbians (homosexual women designation) in the novels are undergoing aberrant sexual activity and feel comfortable with that orientation. This figure are not in conflict with himself and not trying to change their orientation to be normal.